2019
DOI: 10.2217/imt-2019-0061
|View full text |Cite
|
Sign up to set email alerts
|

First-Line Pembrolizumab Monotherapy for Metastatic Pd-L1-Positive Nsclc: creal-World Analysis of Time on Treatment

Abstract: Aim: To determine real-world time on treatment (rwToT) with first-line pembrolizumab monotherapy for metastatic non-small-cell lung cancer (NSCLC) with programmed death ligand-1 (PD-L1) tumor proportion score (TPS) ≥50%. Methods: The Kaplan–Meier rwToT was estimated from electronic health record data for adults who initiated first-line pembrolizumab monotherapy for stage IV, PD-L1 TPS ≥50% NSCLC, with negative/unknown EGFR/ALK aberrations, and ≥6 months’ follow-up until database cutoff. Results: A total of 386… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 26 publications
4
36
1
Order By: Relevance
“…They reported a median rwTOT of 6.9 months vs a median TOT of 7.9 months in KEYNOTE-024 and 6.6 months in KEYNOTE-042. The median TTD of 3.5 months with IO monotherapy in our study was considerably shorter than the Velcheti et al (2019) estimates.…”
contrasting
confidence: 75%
See 2 more Smart Citations
“…They reported a median rwTOT of 6.9 months vs a median TOT of 7.9 months in KEYNOTE-024 and 6.6 months in KEYNOTE-042. The median TTD of 3.5 months with IO monotherapy in our study was considerably shorter than the Velcheti et al (2019) estimates.…”
contrasting
confidence: 75%
“…However, few studies have examined the real-world treatment patterns and clinical outcomes of these therapies. These studies have mostly included patients with previously treated advanced NSCLC, lacked comparisons between treatments, and/or limited the patient population to those with PD-L1 expression (Khozin et al 2018;Molife et al 2019;Nadler et al 2018;Schwartzberg et al 2019;Velcheti et al 2019;Weis et al 2019). Further research on IO use in patients with advanced NSCLC treated in the community oncology setting is needed, as there may be differences in real-world clinical outcomes compared with clinical trial outcomes due to underlying variation in patient populations and methodology (Khozin et al 2019a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pembrolizumab is a humanized antibody used in cancer immunotherapy to treat melanoma, lung cancer, head and neck cancer, Hodgkin’s lymphoma, and stomach cancer [5355]. Pembrolizumab is a first-line treatment for NSCLC if cancer cells overexpresse PD-L1 and have no mutations in EGFR or in anaplastic lymphoma kinase [56, 57]. Large randomized clinical trials indicated that NSCLC patients treated with nivolumab and pembrolizumab (both approved by the US FDA in 2014) showed increased overall survival compared with docetaxel, the standard second-line treatment [58].…”
Section: Clinical Applications and Market For Therapeutic Antibodiesmentioning
confidence: 99%
“…In addition, DNA mismatch repair (MMR) deficiency is an important factor for immune checkpoint inhibitor sensitive mechanism in solid tumors [10,11]. Pembrolizumab, a humanized monoclonal antibody against PD-1, has been reported to have strong antitumor activity in advanced non-small-cell lung cancer (NSCLC) [5,12], although it has not shown sufficient therapeutic effects in PC. A case of UCOGC that was curatively resected following pembrolizumab monotherapy that was highly effective for metastatic lung cancer is presented.…”
Section: Introductionmentioning
confidence: 99%